Development And Assessment Of An X-Ray Fluorescence System For In Vivo Studies - Jaafar, Wan Salwani (2009)
X-ray fluorescence (XRF), which is a standard elemental analysis technique, was investigated for the purpose of measuring elements in vivo. An XRF system comprising of an excitation source, sample and a detection system in a 90° geometry was developed and optimized by simulations using the Monte Carlo code, Monte Carlo N-Particle version 5 (MCNP5). For optimal use, the grazing angle of the sample is at 15° and the source-to-sample distance (SSD) and sample-to-detector distance (SDD) were at minimum values. For experimental verification, a physical system almost similar to the simulated system was set up at the Biophysics Laboratory, School of Physics, USM